101 years of the psychiatric ward and the psychiatric hospital in Radom (1912-2013) - Kosińska, Bożena (Polish Journal of Public Health, 2013)
Introduction. In the context of ongoing changes in the organization of psychiatric care announced by the National Mental Health Programme for 2011-2015, changes in psychiatric care in the Radom region over the last hundred years have been presented. Aim. Presentation of the activities of institutional psychiatric care in the long term and to indicate the necessity of functioning of the psychiatric inpatient departments. Material and methods. Analysis of documents, mainly statistical and reports concerning the activities of mental health care in Radom. Conclusions. Psychiatric Hospital in Radom is one of the largest hospitals in Poland. It supports the area of the former province of Radom inhabited by more than half a million people and has a rich human resources potential and interesting infrastructure. However, the unceasing progress in medicine forces continuous investment in medical staff in order to increase knowledge and improve skills that are necessary to maintain a high quality of provided medical services and the needs of teaching and research. The increase in the number of admissions of patients in the last decade (2001-2010) compared to the previous decade (1991-2000) was 27%, while the number of admissions of patients to the psychiatric wards has increased about 43.5% and was the highest in the history of the hospital. Dynamics of admissions with simultaneously reduced length of hospitalization requires further, in-depth analysis. The creation of the Chronic Psychiatric Medical Home Care in 2001 with 100 beds and its extension in just a few years has increased the number of beds to 235. Moving the care towards psychiatric long-term care demonstrates the growing needs in this area and the failure of the system to provide community psychiatric care in the Radom region.